Posterior Reversible Encephalopathy Syndrome – A Rare Complication after Methylprednisolone (Bangladesh Journal of Medicine, 2020)
Posterior reversible encephalopathy syndrome (PRES) is a rare neurological complication. It can occur as a complication of hypertensive disease of pregnancy, autoimmune disorder or after immunosuppressant. Typical imaging features of PRES are bilateral symmetrical involvement of parietal and occipital lobe. Here, we reported a case of PRES after methylprednisolone.Bangladesh J Medicine Jan 2020; 31(1) : 41-42